If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8 = 2 Reorder the terms: -8 + 2x = 2 Solving -8 + 2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2x = 2 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 2 + 8 2x = 2 + 8 Combine like terms: 2 + 8 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 3(3x+2)=34-x | | 7x-6-(x+2)=4x-2*3 | | x^3-6x^2-3x+10=0 | | -.5x=4x+18 | | 7x+6-(x+2)=4x-2*3 | | 60+44x=32x+96 | | 7-6k+3k-5= | | 7x+6+(x+2)=4x-2*3 | | -8-5y=15-d | | 24+3+12x=10+4x-3x | | 10+971(1673%10)= | | x^3-6x^2-3x-16=0 | | x^3-6x^2-3x-10=0 | | 3.2z=14 | | x^3-6x^2+3x-16=0 | | 8y+8-3y+6=2y+14 | | 44x=32x | | 3=7b+13-2b | | 6=-2n+s | | 4x^2+6x-2=x^2-2x+1 | | 4x^2+6x-2=x^2-2x+2 | | kx^2+12x+12=0 | | 0=8x-(3-z) | | -y-8+8y=-9+5y+1 | | 2x-6-4x-16=4x-1*3 | | 6a-11=19 | | 3x^2-kx+30=0 | | 6*(-1)=7-4y | | 2*x+4=6 | | -8(x-4)=4(x-12) | | 1+5x-2x=-2+3x+15x | | (.02)35+.09(x)=.04(35+x) |